Effect of Olympic weight category on performance in the Roundhouse kick to the head in taekwondo - Estevan, I.; Falcó, C.; Alvarez, O.; Molina-Garcia, J. (Journal of Human Kinetics, 2012)
In taekwondo, kick performance is generally measured using impact force and time. This study aimed to analyse performance in the roundhouse kick to the head according to execution distance between and within Olympic weight categories. The participants were 36 male athletes divided into three categories: featherweight (n = 10), welterweight (n = 15) and heavyweight (n = 11). Our results show that taekwondo athletes in all weight categories generate a similar relative impact force. However, the results indicate that weight has a large impact on kick performance, particularly in relation to total response time.